Constellation ou situation ? - Jean Tain (Recherches Germaniques)
Adorno’s critique of Sartre in the Negative Dialectic (1966) may seem hasty, and mainly driven by his opposition towards Heidegger to whom Sartre is tied. The aim of this paper is to show that the Adornoian critique of Sartreanism nevertheless raises specific issues, such as the role played by the notion of “concrete” in philosophy, and a more accurate understanding of human historicity. Despite an undeniable thematic proximity with Sartre, Adorno prefers to highlight the more complex notion of “constellation” – his answer to what he considers as the overly central position of the human subject defined as freedom in the Sartrean notion of “situation”.